Pengaruh Budaya Organisasi, Gaya Kepemimpinan, dan Kepuasan Kerja terhadap Kinerja Pegawai di SMP Negeri 6 Kota Serang - Titi Stiawati; Ima Maisaroh (Departement of Mathematics Education, 2023)
This study aims to analyze and determine the relationship between the influence of organizational culture, leadership style, and job satisfaction on employee performance at SMP Negeri 6 Kota Serang. The approach used is quantitative with an associative type, while data collection is done through literature and questionnaires which are measured using a Likert scale. The sample in this study was all staff and teachers at SMP Negeri 6 Kota Serang with a total of 30 people. Data testing was carried out through validity testing, reliability testing, classical assumption testing, multiple linear regression testing, and hypothesis testing with the help of software called Statistical Program for Social Science (SPSS) version 24. The results showed that: (1) There is a positive influence and partially significant on organizational culture on employee performance at SMP Negeri 6 Kota Serang; (2) There is a positive and significant effect partially on satisfaction with the performance of employees of SMP Negeri 6 Kota Serang; (3) There is a positive and significant influence partially on leadership on the performance of employees of SMP Negeri 6 Kota Serang; (4) There is a significant influence simultaneously on organizational culture, leadership style, and job satisfaction on the performance of employees of SMP Negeri 6 Kota Serang.